Pembuatan Pangkalan Data Elektronik Kelurahan Muktiharjo Kidul Pedurungan Semarang - Setyoningsih Wibowo; Khoiriya Latifah; Noora Qotrun Nada (Universitas PGRI Semarang, 2016)
Abstract - The advancement of information technology and communication affect the development of storage technology (archival) where archives have an important role in every organization, as well as government and private offices. This research aims to design a system that is easily understood and implemented to help device performance villages become more effective and efficient. This research works preliminary study in the design manufacture electronic database. The subjects of this study is Muktiharjo Kidul village Pedurungan Semarang. This research object is the manufacture of electronic database. The technique used in this study using a system called the System Development Life Cycle (SDLC) is the process of making and editing systems as well as the models and methods used to develop the system. The result of this research is the creation of an electronic database system and the system has been designed to facilitate the performance of the device and can diimplentasikan village well. Based on the results of this study concluded created database aplication can be used to handle the data entry process, data changes, deletions and population data search. Keywords: database, SDLC, Muktiharjo Kidul, access